Estudos genéticos e comportamentais de formigas carpinteiras Camponotus atriceps Smith (Hymenoptera, formicidae) - Marcolino, Marcus Teixeira (1999)
C. atriceps ants have shown exponential growth in anthropic environments. Under laboratory conditions it was possible to verify that the colonies are founded claustrally, by a single queen (Haplometrose). It was also observed the formation of monogenic colonies (M) from polygenic colony (P), by sociotomy. Workers, both in M ​​and P, had a more homogeneous distribution of tasks. Parental care behavior was characteristic in workers In P, communication was more intense in both soldiers and workers. Possibly parental recognition is important for individuals of eusocial species. Multivariate statistical analysis carried out, using Measures made in the head region of workers and soldiers allowed the defection of differences in variability between M and P colonies. The number of chromosomes was also determined, being on 20. Despite the knowledge obtained on this ant, further studies on its biology are needed. Especially in field conditions.